Teachers’ Perceptions of Translanguaging in EFL Classroom - Yoskapela, Yoskapela; Amnah, Amnah; Misrita, Misrita; Akhmad Fauzan, Akhmad Fauzan (Universitas Muhammadiyah Semarang, 2024)
Translanguaging, as a practice, involves the utilization of two or more languages at the same time for communication among bilingual and multilingual individuals. By incorporating translanguaging strategies into teaching pedagogy, teachers can bridge linguistic gaps for Foreign Language learning in the classroom. However, varying perceptions among English as a Foreign Language (EFL) teachers can create barriers that prevent students from fully utilizing translanguaging. To gain a deeper understanding of this issue, the researchers take initiative to investigate the perceptions of Indonesian EFL teachers at a primary school in Palangka Raya, Indonesia. This qualitative research utilized semi-structured interviews to explore four EFL teachers' perspectives on this topic. The findings reveal a generally positive perception of EFL teachers who implement translanguaging strategies such as student-centeredness, collaboration, contextual clues, and two-way translation in their teaching pedagogy. The results of this research hold significance for individuals involved in the education sector, offering valuable information on how to design EFL lessons that utilize translanguaging techniques to cater to the needs of young (EFL) students.